Risk Factors for Mortality in Reoperations for Pediatric and Congenital Heart Surgery in a Developing Country (2017)
BACKGROUND: The survival of patients with congenital heart disease has increased in the recent years, because of enhanced diagnostic capabilities, better surgical techniques, and improved perioperative care. Many patients will require reoperation as part of staged procedures or to treat grafts deterioration and residual or recurrent lesions. Reoperations favor the formation of cardiac adhesions and consequently increase surgery time; however, the impact on morbidity and operative mortality is certain. The objective of the study was to describe the risk factors for mortality in pediatric patients undergoing a reoperation for congenital heart disease.METHODS: Historic cohort of patients who underwent reoperation after pediatric cardiac surgery from January 2009 to December 2015. Operations with previous surgical approach different to sternotomy were excluded from the analysis.RESULTS: In seven years, 3,086 surgeries were performed, 481 were reoperations, and 238 patients fulfilled the inclusion criteria. Mean number of prior surgeries was 1.4 ± 0.6. Median age at the time of reoperation was 6.4 years. The most common surgical procedures were staged palliation for functionally univentricular heart (17.6%). Median cross-clamp time was 66 minutes. Younger age at the moment of resternotomy, longer cross-clamp time, and Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery Congenital Heart Surgery (STAT) Mortality Categories risk category greater than three were risk factors for mortality. The number of resternotomies was not associated with mortality. Mortality prior to hospital discharge was 4.6%, and mortality after discharge but prior to 30 days after surgery was 0.54%. Operative mortality was 5.1%.CONCLUSIONS: Resternotomy in pediatric cardiac surgery is a safe procedure in our center.